Towards a systematic theology of the body - Spinsanti, Sandro (Medicina e Morale, 2024)
Between the two fundamental ways of experiencing one's body, as highlighted by philosophical reflection inspired by phenomenology, the needle of the theological compass points towards the pole of the lived body. Phenomenology has opened up, in contrast to dominant conceptions, the experience of corporeity as a new terrain of research.